What outcomes should researchers select, collect and report in pre‐eclampsia research? A qualitative study exploring the views of women with lived experience of pre‐eclampsia. (24th February 2019) - Duffy, JMN; Thompson, T; Hinton, L; Salinas, M; McManus, RJ; Ziebland, S; ,
Abstract : Objective: To identify outcomes relevant to women with lived experience of pre‐eclampsia. Design: Qualitative interview study. Setting: A national study conducted in the United Kingdom. Sample: Purposive sample of women with lived experience of pre‐eclampsia. Methods: Thematic analysis of qualitative interview transcripts. Results: Thirty women with lived experience of pre‐eclampsia were interviewed. Thematic analysis identified 71 different treatment outcomes. Fifty‐nine of these had been previously reported by pre‐eclampsia trials. Outcomes related to maternal and neonatal morbidity, commonly reported by pre‐eclampsia trials, were frequently discussed by women with lived experience of pre‐eclampsia. Twelve outcomes had not been previously reported by pre‐eclampsia trials. When compared with published research, it was evident that the outlook of women with lived experience of pre‐eclampsia was broader. They considered pre‐eclampsia in relation to the 'whole' person and attached special significance to outcomes relating to emotional wellbeing and the future health, development and wellbeing of their offspring. Conclusions: Selecting, collecting and reporting outcomes relevant to women with pre‐eclampsia should ensure that future pre‐eclampsia research has the necessary reach and relevance to inform clinical practice. Future core outcome set development studies should use qualitative research methods to ensure that the long list of potential core outcomes holds relevance to patients. Tweetable abstract: What do women want? A national study identifies key treatment outcomes for women with pre‐eclampsia. Next step: @coreoutcomes for #preeclampsia @NIHR_DC. Tweetable abstract: What do women want? A national study identifies key treatment outcomes for women with pre‐eclampsia. Next step: @coreoutcomes for #preeclampsia @NIHR_DC. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights15616